PENGARUH PENCUCIAN DETERJEN TERHADAP HASIL EKSTRAKSI DNA SPERMATOZOA PADA KAIN KATUN - Gunardi, Christian Subagya; Junitha, I Ketut; Narayani, Inna (SIMBIOSIS, 2022)
The presence of spermatozoa DNA is reliably counted as a solid evidence when dealing with rape cases. However, police department often finds difficulties to obtain it, mainly because it has been destroyed by the perpetrator. Such act can be done by washing semen stains on the clothing with detergent. The purpose of this research is to analyze the impact of detergent as a washing property towards spermatozoa DNA extract on a cotton fabric. Observed variables in this study are quantity and quality of spermatozoa DNA extract from semen stain on cotton fabric. Samples are divided based on two separate treatments; detergent-washed and unwashed. Furthermore, samples are stored with different storage time. This research applied two methods; DNA extraction using kit ( Roche ) and DNA quantification using spectrophotometer Nanodrop . The research was held at Biomedic Laboratory, Faculty of Medicine, Udayana University, Denpasar with ethical clearance. Seminal plasma sampel was obtained from a donor with informed consent. This research showed that seminal stain washing on cotton fabric doesn't remove the DNA until two-week-storage time.